Genome editing approaches using reproductive cells/tissues in flowering plants - Toda, Erika; Kato, Norio; Higashiyama, Tetsuya; Okamoto, Takashi (Frontiers in Genome Editing, 2023)
Targeted mutagenesis via programmable nucleases including the clustered regulatory interspaced short palindromic repeats (CRISPR)/CRISPR-associated protein 9 (Cas9) (CRISPR/Cas9) system has been broadly utilized to generate genome-edited organisms including flowering plants. To date, specific expression of Cas9 protein and guide RNA (gRNA) in reproductive cells or tissues is considered one of the most effective genome-editing approaches for heritable targeted mutagenesis. In this report, we review recent advances in genome editing methods for reproductive cells or tissues, which have roles in transmitting genetic material to the next generation, such as egg cells, pollen grains, zygotes, immature embryos, and shoot apical meristems (SAMs). Specific expression of Cas9 proteins in initiating cells efficiently induces targeted mutagenesis via Agrobacterium-mediated in planta transformation. In addition, genome editing by direct delivery of CRISPR/Cas9 components into pollen grains, zygotes, cells of embryos and SAMs has been successfully established to generate genome-edited plant lines. Notably, DNA-free genome editing by the delivery of Cas9-gRNA ribonucleoproteins (RNPs) is not associated with any legislative concerns about genetically modified organisms. In summary, the genome editing methods for reproductive cells or tissues have enormous potential for not only basic studies for plant reproduction but also applied sciences toward molecular plant breeding.